Characterization of Microstructure and Mechanical Properties of Mg–Y–Zn Alloys with Respect to Different Content of LPSO Phase. Issue 1 (31st August 2017) - Horváth, Klaudia; Drozdenko, Daria; Daniš, Stanislav; Garcés, Gerardo; Máthis, Kristián; Kim, Shae; Dobroň, Patrik
Abstract : The Mg–Y–Zn alloys with different contents of alloying elements are extruded at an extrusion ratio of 4:1 at 350 °C. The microstructure of the alloys is of an inhomogeneous character showing fine grains produced due to dynamic recrystallization and coarse original grains elongated along the extrusion direction (ED). Moreover, Y and Zn form a long‐period stacking‐ordered (LPSO) phase whose volume fraction increases with their increasing content in the alloy. All investigated alloys exhibit distinct fiber textures with basal planes oriented parallel to ED. It is seen that increasing content of alloying elements leads to a weaker texture. Compression tests with concurrent acoustic emission (AE) measurements are performed along ED at room temperature and a constant strain rate in order to reveal active deformation mechanisms in the alloys and to relate them to their mechanical properties. The AE response is also discussed with respect to the volume fraction of the LPSO phase. Abstract : Mg–Y–Zn alloys with a various content of alloying elements and thus a different volume fraction of the LPSO phase are investigated during compression along extrusion direction. Acoustic emission (AE) technique is applied for revealing the influence of the volume fraction of the LSPO phase on active deformation mechanisms. The volume fraction of the LPSO phase increases at the expense of the unrecrystallized grains what leads to suppressing the twinning activity.